Stefansson and the Canadian Arctic - Diubaldo, Richard J. (desLibris. Books collection., 1998)
"Was Vilhjalmur Stefansson a prophet or a profiteer, a victim or a villain? Stefansson and the Canadian Arctic reveals the truth about this fascinating and complex Northern pioneer." "Vilhjalmur Stefansson (1879-1962) was Canada's greatest modern arctic explorer as well as a theorist, author, and pioneer ethnologist. Ranked with Amundsen, Peary, and Shakleton he discovered some of the last major land masses in the Arctic, yet by the mid-1920s he had become persona non grata in Canada, accused of lying to members of his expeditions about the perils they faced and leading many of them to their deaths. Admirers consider Stefansson a prophet and a visionary for giving Canada a sense of its Northern destiny, while critics consider him a charlatan, a manipulator, and a murderer."--Jacket